Implementation of Academic Supervision in Improving Teachers' Pedagogic Competence - Hasbi, Muh (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2021)
The background of this research is implementing academic supervision in elementary schools, teacher academic supervision is important because it affects the level of teacher ability. Based on this, of course, the competence of teachers in teaching is very influential, especially in increasing student creativity. Through School Action Research (PTS), principals can improve the way teachers teach in the classroom. Based on the above background, the writer tries to improve the class teacher's ability in learning mathematics through academic supervision. This research is a type of school action research (PTS) which is conducted in two cycles with 3 teachers as the research subject, which is determined based on the results of pre-cycle observations. Data collection was carried out by observation techniques, Furthermore, the data were analyzed using quantitative descriptive analysis. The results of this study indicate that the application of academic supervision with classroom observation techniques can improve the ability of SDI Sanging-Sanging teachers.